Telephone Conversation Opening in Iran: Males and Females in Focus - Dabaghi, Azizollah; Khadem, Akram (Mediterranean Journal of Social Sciences, 2012)
This paper aims to compare the structure of telephone conversation opening in Iran between males and females withparticular attention to the â€œhow are youâ€ sequence. Natural data are 30 recorded telephone conversations by both males and females indifferent age groups. The data are transcribed for analysis to see how these two groups perform their telephone conversation openings.Due to the differences in their nature, there seems some considerable differences will be observed between the males and the femalesnot only in the â€œhow are youâ€ section but also in the selection of words.